Rozwiązywa(nie) zadań tekstowych – stare wyzwania i nowe potrzeby edukacji wczesnoszkolnej - Nawolska, Barbara; Żądło-Treder, Joanna (Studia Edukacyjne, 2020)
Every human needs the ability to solve problems. In early childhood education, the development of this skill can and should be implemented by solving text tasks. Meanwhile, according to a variety of analyses, a significant number of students are unable to solve these tasks. This is most likely the result of insufficient mathematical competencies of teachers in early school education and related teaching errors, mainly involving calculating exercises and solving tasks according to patterns. At the same time, students who are in fact unable to solve tasks but only limit themselves to the use of learned patterns, in non-standard task situations (not practiced at school) do quite well.